Geopolitical Influence of Afghanistan’s Neighbors on the Country's Domestic and Foreign Policies - Fayaz Gul Mazloum Yar; Noorani Wafa (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Afghanistan is one of the most populous countries in the world. This paper examines the geopolitical impacts of Afghanistan's neighboring countries on its domestic and foreign policies, highlighting their critical role in shaping the country's policies amidst regional and global developments. The study employs a mixed-methods approach, integrating both quantitative and qualitative data to provide a comprehensive understanding of the subject. The results indicate that economic and trade collaborations between Afghanistan and its neighbors, particularly China and Pakistan, have significantly contributed to Afghanistan''s economic and infrastructural development. The findings also indicate that cultural and historical ties with Iran and India have played a pivotal role in strengthening regional security and fostering regional cooperation with Afghanistan. In addition, interviews and document content analysis demonstrate the critical role of Central Asian countries in enhancing regional security. The research seeks to provide recommendations for fostering better cooperation and more effective policy frameworks in Afghanistan.